2020
DOI: 10.3389/fphys.2020.580687
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle in Insect Energy Homeostasis

Abstract: Maintaining energy homeostasis is critical for ensuring proper growth and maximizing survival potential of all organisms. Here we review the role of somatic muscle in regulating energy homeostasis in insects. The muscle is not only a large consumer of energy, it also plays a crucial role in regulating metabolic signaling pathways and energy stores of the organism. We examine the metabolic pathways required to supply the muscle with energy, as well as muscle-derived signals that regulate metabolic energy homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
(125 reference statements)
0
27
0
Order By: Relevance
“…Additionally, as we mentioned previously, insulin is highly involved in energy homeostasis, inter alia , by increasing the rate of glycolysis in muscles by stimulating hexokinase and 6-phosphofructokinase activity and stimulating glycogen synthesis ( Dimitriadis et al, 2011 ). Recent reports concerning the role of ILPs in the regulation of the functioning of insect muscles showed that, similar to vertebrate insulin, these neuropeptides are also important for the regulation of growth and ageing, and the control of energy storage in the muscles ( Bai et al, 2013 ; Bretscher and O’Connor, 2020 ).…”
Section: Metabolic Processes Regulated By Ilpsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, as we mentioned previously, insulin is highly involved in energy homeostasis, inter alia , by increasing the rate of glycolysis in muscles by stimulating hexokinase and 6-phosphofructokinase activity and stimulating glycogen synthesis ( Dimitriadis et al, 2011 ). Recent reports concerning the role of ILPs in the regulation of the functioning of insect muscles showed that, similar to vertebrate insulin, these neuropeptides are also important for the regulation of growth and ageing, and the control of energy storage in the muscles ( Bai et al, 2013 ; Bretscher and O’Connor, 2020 ).…”
Section: Metabolic Processes Regulated By Ilpsmentioning
confidence: 99%
“…Despite the participation of ILP signalling in insect muscle growth and functioning, regulation of the availability of energy substrates stored in insect muscles by ILPs is no less important ( Bretscher and O’Connor, 2020 ). The main energy substrate accumulated in insect muscles is glycogen.…”
Section: Metabolic Processes Regulated By Ilpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycolysis is a major metabolic pathway that plays a vital role in core energy processing reactions, and as a source of metabolites for other biochemical processes. For insects, there is a high utilization of glucose in flight muscle located in the thorax [24]. As a result, the activities of glycolytic enzymes are increased in insect flight muscle compared to vertebrate muscle tissue [25].…”
Section: Contextmentioning
confidence: 99%